Translation of Indonesian Economic Terms into English in Annual Reports - I Dewa Gede NuhurAdhi Basma (Program Magister Linguistik Universitas Udayana, 2021)
Translation becomes very important in this fast growing information era in which people from different speaking countries need more resources to develop their knowledge. Banks are one of field that demand the assistance from translators to translate their annual reports. However, it is not as easy as it looks since translators may find issues in translating an annual report into target languages because he/she needs to find equivalent translation of source language for such terms into target languages. The aim of this study is to analyze the procedures applied in translating the Indonesian economic terminologies into English in the annual report. This paper is a library research where the data is in the form of documents or printed out texts. The method that is implemented in analyzing the data in this study is the qualitative one proposed by Creswell (2009). There were eight procedures applied by the translator in translating the Indonesian economic terms into English in the annual report. They are transference, naturalization, through translation, transposition or shifts, modulation, recognize translation, synonym and couplets.